Balancing Work And Life - Holden, Robert, 1965-; Renshaw, Ben. (London : Dorling Kindersley, 2002)
Balancing Work and Life shows how to manage life successfully by creating a healthy balance between personal and working life.
Includes index.
Keywords: Work and family; Self-actualization (Psychology); Psychology